Upaya Peningkatan Sirkulasi Darah Perifer Pada Pasien Diabetes Melitus Tipe 2 Melalui Edukasi Therapeutic Exercise Walking dan Rendam Kaki Air Hangat - Deski, Febby Irianti; Yendrial, Vania Aresti (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Diabetes mellitus (DM) type 2 is a metabolic disease characterized by impaired glucose metabolism and has the potential to cause various complications, including impaired peripheral blood circulation. Poor blood circulation can cause Peripheral Artery Disease (PAD), which carries the risk of ulcers, gangrene, and slow wound healing in patients with DM type 2. This Community Service Activity aims to increase the knowledge of DM type 2 patients to improve peripheral blood circulation and prevent diabetic ulcers by providing education on therapeutic exercise walking and warm water foot soaks in the XXX Community Health Center work area. The activity was carried out in January 2025 in the XXX Community Health Center Work Area, Padang City. The activity methods included health education through counseling using PowerPoint media, leaflet distribution, as well as interactive discussions and question and answer sessions. To evaluate the increase in participants' understanding, instruments were used in the form of pre-tests and post-tests. The results of the activity evaluation showed an increase in participants' understanding of therapeutic exercise walking and warm water foot soaks to prevent diabetes complications from 45% to 85%.